The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1093/jjco/hyt033
|View full text |Cite
|
Sign up to set email alerts
|

A Large Cell Neuroendocrine Carcinoma of the Gall Bladder: Diagnosis with 18FDG-PET/CT-guided Biliary Cytology and Treatment with Combined Chemotherapy Achieved a Long-term Stable Condition

Abstract: Poorly differentiated neuroendocrine cell carcinomas of the gallbladder are rare and patients with such tumors have a poor prognosis. We describe a 64-year-old male with a large cell neuroendocrine carcinoma of the gallbladder and multiple lymph node metastases. Diagnostic excisional biopsy of the left axillary lymph nodes revealed atypical cells with predominantly large-sized round-to-oval nuclei, proliferating in a solid and focal nesting pattern. The tumor cells were positive for synaptophysin and chromogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…3,[6][7][8][9][10][11]23 It is not possible to preoperatively differentiate between gallbladder adenocarcinoma and gallbladder neuroendocrine carcinoma (NEC) with imaging techniques because other neoplasms (i.e., hepatocellular carcinoma, cholangiocarcinoma, hepatic metastasis involving the gallbladder, and gallbladder adenocarcinoma) may have similar patterns. 3,[6][7][8][9][10][11]23 Ultrasonography has low sensitivity (44%) for the identification of gallbladder cancer. 13 In our case, abdominal ultrasonography and radiologic findings revealed a 25-mm gallbladder tumor with suspected malignancy.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…3,[6][7][8][9][10][11]23 It is not possible to preoperatively differentiate between gallbladder adenocarcinoma and gallbladder neuroendocrine carcinoma (NEC) with imaging techniques because other neoplasms (i.e., hepatocellular carcinoma, cholangiocarcinoma, hepatic metastasis involving the gallbladder, and gallbladder adenocarcinoma) may have similar patterns. 3,[6][7][8][9][10][11]23 Ultrasonography has low sensitivity (44%) for the identification of gallbladder cancer. 13 In our case, abdominal ultrasonography and radiologic findings revealed a 25-mm gallbladder tumor with suspected malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Okuyama et al 10 previously reported that 18FDG-PET/CT was useful for confirmation of the origin of lymph node metastases and the effective clinical diagnosis of patients with gallbladder LCNEC. 10 Nakagawa et al 14 suggested that cytologic screening had an advantage over histologic approaches based on hematoxylin and eosin (HE) staining with respect to qualitatively diagnosing gallbladder LCNEC. Conventional HE staining requires paraffin embedding of the tissue, which involves dehydration and deparaffinization during processing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations